The antioxidant and in vitro hepatoprotective activities of some chemical fractions from Phyllanthus reticulates Poir. plant - Cúc, Nguyễn Thị; Trâm, Nguyễn Công Thùy; Phương, Đỗ Thị; Phương, Vũ Thị Thu; Nga, Nguyễn Thị; Truan, Gilles; Thảo, Đỗ Thị (Vietnam Journal of Biotechnology, 2018)
The Phen-den plant (Phyllanthus reticulatus Poir.) has been widely used in Vietnamese tradional medicine for detoxification, antiseptic, diuretic, anti-inflammation treatments…However, there is still lack of studies on this plant’s antioxidant and in vitro hepatoprotective activities in Vietnam. Recently, the use of liver enzymes such as CYP450 reductase (CPR) in determining the in vitro hepatoprotective activities of potential compounds, which are originated from herbal plants, is increasing based on its high efficiency and short duration. Furthermore, the other in vitro assays such as DPPH (2,2-diphenyl-1-picryl-hydrazylhydrate) scavenging, inhibition of lipid peroxidation (MDA) are popularly employed for determination of antioxidant activities. With the success in isolation of CPR from Saccharomyces cerevisiae WR1A2 strain (5 litres/batch), we set up the assay for screening potential samples which could be able to induce CPR for in vitro hepatoprotective action. The obtained results from this CPR screening assay showed the similarity to those of other popular antioxidant assays such as DPPH or MDA. The resulted from our assay showed that the water extract of Phen-den plant had the highest ability to induce CPR supporting the hepatoprotective activities. Also, the water extract, EtOAc extract and total extract exhibited very strong antioxidant activities through DPPH scavenging assay and inhibition of lipid peroxidation with the SC50 values ranging at 13.84 µg/ml, 37.64 µg/ml, 28.31 µg/ml and the IC50 values ranging at 5.99 µg/ml, 4.77 µg/ml, 27.58 µg/ml, respectively